The Correlation in the Arabic Tongue Lesson - العاني, لمى فائق جميل (Al-Adab Journal, 2019)
The term "Correlation" is one of the terms of scientific research and tongue at the same time and it means according to Dr. Munther Ayyash "Where is a case that needs to be resolved to two sciences because it refers to two things that are similar, one becomes a condition of the other." The fundamentalists have replaced that , the science incorporated for them , and they are in comprehensive vision, so the semantic search has become a product of that, have addressed different linguistic phenomena, all in order to reach the deep Quranic meaning, understand the sacred text and derive the provisionsThe intersection of science has a long history in Arabic language , as the Arabic language at the beginning of its inception being a science that had begun with holy Quran and its interpretation, there was a need to know the meanings of the Qur'anic vocabulary, the grammatical formulas and the weights. The Qur'anic lesson has been linked to the Arabic language and has influenced and influenced it, and those who interpret the holy Quran must learn about and be able to teach Arabic language.Not only did in the old Arabic language studies appear in the modern tongue lesson, most of the modern linguists were of multidisciplinary that helped to understand the language and crystallized general language theories that confirmed the relationship between language and other sciences, to this day, we find the link of language in several topics such as: Sociology of social language and psychology and without the cross-fertilization of language with others, this science would not have been that founded for the curriculum and theories represented the foundation pillar in the tongue lesson.